A Prospective study on the assessment of risk factors for type 2 diabetes mellitus in outpatients department of a south Indian tertiary care hospital: A case-control study - SIVAPRASAD PENDYALA,; SIDDHARTHA NUTHAKKI,; CHARAN VALLABHU,; NAVEENBABU KILARU,; SIVA R CHALLA,; Pingili, Ravindrababu (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Background: Type 2 diabetes mellitus (T2DM) is the most general type of diabetes. In India, the risk factors (modifiable and nonmodifiable) for diabetes are seen more frequently and there is lack of perception about this problem. Objective: The objective of the study was to assess the incidence and risk factors for T2DM in a south Indian tertiary care hospital. Materials and Methods: A prospective study was conducted on 1161 subjects (with or without T2DM) from November 2014 to April 2015 in general medicine department of Dr. Pinnamaneni Siddhartha Institute of Medical Sciences and Research Foundation, Andhra Pradesh, south India. Chi-square test was used to evaluate the incidence of T2DM and odds ratios were calculated in univariate logistic regression analysis for risk factors. Results: T2DM was significantly higher in the subjects of age above 41 years (86.3%, P<0.0001), married (95.4%, P=0.002), educators (degree and above, 13.2%, P<0.0001), known family history (50.8%, P<0.0001), BMI (>25 kg/m2,58.7%; P<0.0001), Govt. job holders (5.5%, P<0.0001), business people (12%, P<0.0001), house wives (38.3%, P<0.0001), high economic status (34.9%, P<0.0004), preexisting hypertension (40.2%, P<0.0001), urban residence (50.4%, P<0.0001), physical inactivity (45.3%, P<0.001), stress (61.0%, P=0.01), consumption of tea and coffee (daily thrice or more, 6.3%, P=0.0003), soft drinks (weekly thrice or more, 4%, P=0.0008) and junk foods (weekly thrice or more 2.6%, P=0.025) than non-diabetic subjects. Univariate logistic regression analysis showed that the age (above 41 years), marital status, education, family history, BMI (>25 kg/m2), high economic status, co-morbidities (hypertension and thyroid disorders) urban residence, physical inactivity, stress, consumption of tea and coffee (daily thrice or more), soft drinks (weekly thrice or more) and junk foods are the significantly risk factors for T2DM. Conclusion: The present study results suggested that beware of hypertension, thyroids disorders, physical inactivity, stress, soft drinks and junk foods, which are major risk factors of T2DM.Â 